'Let us understand each other and work together in the child's best interest' – Exploring the narratives of newly arrived refugee parents in Sweden. (March 2021) - Baghdasaryan, Z.; Lampa, E.; Osman, F.
Abstract: Complex and multi-layered socio-economic and cultural challenges face refugee parents resettling in a new country. The aim of this study was to describe refugee mothers and fathers' experiences of parenthood by lifting up their own voices, illuminating the challenges they face and laying the basis for designing interventions to provide well-informed and culturally tailored support programmes for families in need. The study combined narrative research with focus group discussions with 50 refugee mothers and fathers in Sweden. Data were analysed inductively using thematic analysis. The main theme identified: Navigating the changing landscape of parenthood, captured refugee parents' experiences of navigating their parenthood through the new socio-political, cultural, and economic setting in Sweden. The study results demonstrated how acculturation challenges undermined the role of parents, threatened the family cohesion and led to alienation of children from their parents. Despite the plethora of challenges faced by families, parents struggling to navigate two differing cultural paradigms, envisioned a path of dialogue and reconciliation between newcomers and the host society as a way to foster true integration and understanding between immigrant and native communities.